86.6k views
3 votes
Factorise
2х^2 — 3x— 14

1 Answer

7 votes

Answer:

(x + 2)(2x - 7)

Explanation:

Given

2x² - 3x - 14

Consider the factors of the product of the x² term and the constant term which sum to give the coefficient of the x- term.

product = 2 × - 14 = - 28 and sum = - 3

The factors are - 7 and + 4

Use these factors to split the x- term

2x² + 4x - 7x - 14 ( factor the first/second and third/fourth terms )

= 2x(x + 2) - 7(x + 2) ← factor out (x + 2) from each term

= (x + 2)(2x - 7)

Thus

2x² - 3x - 14 = (x + 2)(2x - 7) ← in factored form

User Viktor Kukurba
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.